2021
DOI: 10.3390/mti5030013
|View full text |Cite
|
Sign up to set email alerts
|

Building an Emotionally Responsive Avatar with Dynamic Facial Expressions in Human—Computer Interactions

Abstract: The role of affect has been long studied in human–computer interactions. Unlike previous studies that focused on seven basic emotions, an avatar named Diana was introduced who expresses a higher level of emotional intelligence. To adapt to the users various affects during interaction, Diana simulates emotions with dynamic facial expressions. When two people collaborated to build blocks, their affects were recognized and labeled using the Affdex SDK and a descriptive analysis was provided. When participants tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This work contributes to the growing field of affective computing, where the goal is to imbue computers and digital interfaces with the ability to recognize and respond to human emotions. The advancements presented in this paper have implications for the design of emotionally engaging avatars in applications ranging from virtual assistants to gaming [4].…”
Section: Literature Surveymentioning
confidence: 99%
“…This work contributes to the growing field of affective computing, where the goal is to imbue computers and digital interfaces with the ability to recognize and respond to human emotions. The advancements presented in this paper have implications for the design of emotionally engaging avatars in applications ranging from virtual assistants to gaming [4].…”
Section: Literature Surveymentioning
confidence: 99%
“…Given numerous human-robot interaction (HRI)-related studies (Jack et al, 2014;Wittig et al, 2015;Mcginn, 2020;Wang et al, 2021), where emotions are managed using Ekman's Facial Action Coding System (FACS) (Ekman and Friesen, 1978), our research focuses on 6 basic emotions: happiness, surprise, disgust, sadness, anger, and fear (Ekman et al, 1969;Piórkowska and Wrobel, 2017).…”
Section: Emotions In Virtual Character Designmentioning
confidence: 99%
“…In a study by Chao et al (2012), the recognition of emotions by the user is included but the communication of emotions by the avatar remains unattended. A comparative analysis by Wang et al (2021) found a greater user receptiveness when using an avatar with emotional responses unlike using an avatar with a flat facial expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge of building an interactive virtual agent differs from that of building an interactive robot. Heting et al [14] discuss the use of virtual agents, specifically avatars, in human-computer interactions. The paper presents an emotionally responsive avatar named Diana, which recognizes human affect and responds with natural facial expressions to improve the user experience in the interaction.…”
Section: Introductionmentioning
confidence: 99%